Chaos [compact disc, unabridged] - Johansen, Iris (Hachette Book Group, 2020)
Aided by billionaire Gabe Korgan, CIA agent Alisa Flynn is determined to rescue schoolgirls kidnapped from their African boarding school. But Alisa is hiding her personal stake in the rescue.